PENGARUH KUALITAS PELAYANAN, SALURAN DISTRIBUSI DAN FASILITAS TERHADAP LOYALITAS PELANGGAN PADA TOKO PUPUK DAN PERTANIAN IWAN JAYA DI CARMEE KABUPATEN BONDOWOSO MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Rizky, Adrian Fahrizal; Hamdun, Edy Kusnadi; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Currently, the era of globalization, development and growth of the global economy today has an impact on increasingly competitive service companies. To win and to remain competitive in this competition, companies must develop the right plan, by trying to satisfy customer needs and desires, provide the best service and provide facilities according to customer needs. So that the company's goal is to obtain maximum profit, and to achieve customer loyalty and form strong relationships with consumers. The aim of this research is to analyze and test the influence of Service quality, Distribution channels and Facilities on Customer loyalty at the Iwan Jaya Fertilizer and Agriculture Shop in Cermee, Bondowoso Regency through Consumer satisfaction as an intervening variable. The populations in this study were customers of the Iwan Jaya Fertilizer and Agriculture Shop. The sampling technique was determined by simple random sampling. The data analysis and hypothesis testing in this research used Structural Equation Analysis - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using Smart PLS 3.0, show that Service quality has a significant positive effect on Consumer satisfaction. The Distribution channels have a positive but not significant effect on Consumer satisfaction. Facilities have a significant positive effect on Consumer satisfaction. The Service quality has a significant positive effect on Customer loyalty. The Distribution channels have a positive but not significant effect on Customer loyalty. The Facilities have a significant positive effect on Customer loyalty. Customer satisfaction has a significant positive effect on Customer loyalty. The results of the indirect influence hypothesis test show that Service quality, Distribution channels, and Facilities have a positive but not significant effect on Customer loyalty through Consumer satisfaction.